Pengelolaan Kelas Bakat Istimewa di SMA Negeri 1 Slogohimo - Suyoto, Suyoto, Prof. Dr Bambang Sumardjoko, Dr. Eko Supriyanto, SH., M.H (2015)
The purpose of this study: to describe the planning, execution, and evaluation of a special talent sports class management in SMA Negeri 1 Slogohimo. Location study is in SMA Negeri 1 Slogohimo. This type of the research is qualitative research. Data collection techniques are using observation, interviews, and document analysis methods. Planning begins from the SWOT analysis is to look at the strengths, weaknesses, opportunities, and constraints of SMA Slogohimo. The potential modals of this school are the physical plane, student achievement, professional trainers, and as well as geographical location. The result of this study is a planning of a special talent sports class management in SMA 1 Slogohimo covers three aspects: the process of student selection, the curriculum, and the facilities and infrastructure. The implementation of sport talent special class management in SMA 1 Slogohimo covers four aspects, namely, schedule, the selection of teachers, the service methods, as well as guidance and counseling services. To assess the success of this program, there are overall evaluations continue at the end of each semester. Having held a sport special talent class for three years, there is a significant increase performance in non-academic achievement in district high school level.